Abnormalities of horizontal gaze. Clinical, oculographic and magnetic resonance imaging findings. II. Gaze palsy and internuclear ophthalmoplegia. Issue 3 (March 1990) - Bronstein, A M; Rudge, P; Gresty, M A; Du Boulay, G; Morris, J
Abstract : The site of lesions responsible for horizontal gaze palsy and various types of internuclear ophthalmoplegia (INO) was established by identifying the common areas where the abnormal MRI signals from patients with a given ocular-motor disorder overlapped. Patients with unilateral gaze palsy had lesions in the paramedian area of the pons, including the abducens nucleus, the lateral part of the nucleus reticularis pontis caudalis and the nucleus reticularis pontis oralis. Patients with abducens nucleus lesions showed additional clinical signs of lateral rectus weakness. Lesions responsible for bilateral gaze palsy involved the pontine tegmental raphe. Since this region contains the saccadic omnipause neurons, this finding suggests that damage to omnipause cells produces slowing of saccades rather than opsoclonus, as previously proposed. All INOs, regardless of the presence of impaired abduction or convergence, had similar MRI appearances. Frequently the lesions in patients with INO, were not confined to the medial longitudinal fasciculus (MLF) but also involved neighbouring structures at the pontine and mid-brain levels. There was a statistically significant association between the clinical severity of the INO and the presence of abnormal abduction or convergence. The findings suggest that the lesions outside the MLF, which may affect abducens, gaze or convergence pathways, are responsible for the presence of features additional to INO, depending on the magnitude of functional disruption they produce.